The Students’ Ability in Identifying Generic Structure of Recount Text - Widya Juli Astria; Sherly Franchisca; Lailatul Husna; Intan Rahmayani (Ikatan Dosen Menulis, 2023)
This research aimed to analyze the ability and difficulty of students inidentifying the generic structure of the recount text. There were some students who had difficulties about the recount text. They did not know the structure of recount text. This research was conducted at SMKN 5 Padang in the 2021/2022 school year. This research used descriptive research. The population of this research were25 students of class XTPM 3 SMKN 5 Padang. The instrumentation of the research was reading test. The results showed that students' reading abilities in the recount text at TPM 3 SMK 5 Padang class could be categorized as good. Based on the data, there were 3 students got excellent (12%), while there were 4 students got very good(16%), then there were 7 students got good (28%), then there were 5 students got sufficient (20%), and last there were 6 students got poor (24%). Based on the research analysis, it can be concluded that students struggled due to lack of vocabulary, and there were some students who did not understand about the text,and had difficulty in determining parts of the generic structure. The researcher suggested to the teacher should give a lot of reading exercises to improve the student's ability in vocabulary and grammar.